1998
DOI: 10.1046/j.1440-1754.1998.00241.x
|View full text |Cite
|
Sign up to set email alerts
|

The use of human glutathione S‐transferase A1 in the detection of cystic fibrosis liver disease

Abstract: Serum hGST A1 measurement increases the sensitivity of detecting hepatic abnormalities when included with clinical and ultrasound evaluation although, in some cases with advanced liver disease, serum hGST A1 may be normal. Conventional liver enzyme tests add little information in the detection of CF liver disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…However, no stratification was undertaken with severity of fibrosis. Two studies have suggested that human glutathione S transferase A1 (GSTA) was superior to conventional transaminases and comparable to ultrasonography in detecting liver disease, but its utility for detecting hepatic fibrosis was not determined as no biopsies were undertaken [24,25]. Serum PIIIP and PH were studied in 44 children with CF, 26 with suggestion of liver disease by clinical and ultrasound abnormalities [21].…”
Section: Discussionmentioning
confidence: 99%
“…However, no stratification was undertaken with severity of fibrosis. Two studies have suggested that human glutathione S transferase A1 (GSTA) was superior to conventional transaminases and comparable to ultrasonography in detecting liver disease, but its utility for detecting hepatic fibrosis was not determined as no biopsies were undertaken [24,25]. Serum PIIIP and PH were studied in 44 children with CF, 26 with suggestion of liver disease by clinical and ultrasound abnormalities [21].…”
Section: Discussionmentioning
confidence: 99%